Investigation of the Changing in Parenting Levels of Fathers in the Covid-19 Process - Işık, Esra (Fırat University, 2023)
The closure of workplaces, schools and childcare centers in accordance with the measures taken within the scope of the Covid-19 pandemic, made it compulsory for family members to spend longer time at home. Although they are involved in every moment of their children’s lives, it is thought that there are changes in fathers’ parenting skills and parenting skill levels due to the increase in the time they spend at home during the pandemic process. Based on this idea, it was aimed to examine the change in parenting levels of fathers during the Covid-19 process. The study group of this research, which was designed according to the survey model and cross-sectional survey design, which is one of the quantitative research methods, consists of 349 fathers who have at least one child between the ages of 4-18. In the analysis of the data, correlation coefficient values and heat map method were used. As a result of the research; fathers’ competency scale scores and demographic variables are only related to educational status; it has been found that fathers spend more time with their children and strengthen their communication with their children and other family members due to the increase in their competence scale scores and the time they stay at home. In the study, it was also found that the stress level experienced by the father affected the behavior and stress level of his child negatively, that there were changes in the parenting skills of the fathers during the pandemic, and that the fathers who felt inadequate in parenting received support mostly from their spouses, and least from family elders and books when they felt inadequate.

Covid-19 pandemi süreci kapsamında alınan önlemler ve tedbirler gereğince iş yerlerinin, okulların ve çocuğun bakımını sağlayan kurumların kapatılması aile bireylerinin evde daha uzun süre zaman geçirmelerini zorunlu kılmıştır. Çocuklarının yaşamlarının her anında yer almalarına karşın pandemi sürecinde evde geçirdikleri sürenin artmasına bağlı olarak babaların ebeveynlik becerilerinde ve ebeveynlik beceri düzeylerinde değişiklikler olduğu düşünülmektedir. Bu düşünceden hareketle araştırmada Covid-19 sürecinde babaların ebeveynlik düzeylerindeki değişimin incelenmesi amaçlanmıştır. Nicel araştırma yöntemlerinden tarama modeline ve kesitsel tarama desenine göre tasarlanan bu araştırmanın çalışma grubunu 4-18 yaş arası en az bir çocuğu olan 349 baba oluşturmaktadır. Araştırmada verilerin analizinde korelasyon katsayısı değerleri ve ısı haritası yöntemi kullanılmıştır. Araştırma sonucunda; babaların yetkinlik ölçeği puanları ile demografik değişkenlerden sadece eğitim durumunun ilişkili olduğu; babaların yetkinlik ölçeği puanları ve evde kalma sürelerinin artmasına bağlı olarak çocuklarına daha çok zaman ayırdıkları, çocukları ve diğer aile bireyleri ile olan iletişimlerini güçlendirdikleri bulgusu elde edilmiştir. Araştırmada ayrıca babanın yaşadığı stres düzeyinin çocuğunun davranışlarını ve stres düzeyini olumsuz yönde etkilediği, pandemi süresince babaların ebeveynlik becerilerinde değişiklikler görüldüğü, kendilerini ebeveynlikte yetersiz hisseden babaların yetersiz hissettikleri durumlarda en çok eşlerinden, en az ise aile büyüklerinden ve kitaplardan destek aldıkları bulgularına ulaşılmıştır.
COVID-19 SÜRECİNDE BABALARIN EBEVEYNLİK DÜZEYLERİNDEKİ DEĞİŞİMİN İNCELENMESİ